Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jamanetworkopen.2021.28817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods to Estimate Low-Density Lipoprotein Cholesterol in Patients With High Triglyceride Levels

Abstract: IMPORTANCE Low-density lipoprotein cholesterol (LDL-C) is typically estimated with the Friedewald or Martin/Hopkins equation; however, if triglyceride levels are 400 mg/dL or greater, laboratories reflexively perform direct LDL-C (dLDL-C) measurement. The use of direct chemical LDL-C assays and estimation of LDL-C via the National Institutes of Health Sampson equation are not well validated, and data on the accuracy of LDL-C estimation at higher triglyceride levels are limited. OBJECTIVE To compare an extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
5
45
1
Order By: Relevance
“…The new Sampson formula reported by Sampson et al is a better alternative for estimating LDL-C than conventional methods ( 18 ). Quite a few studies proved that Sampson's formula is more accurate than Friedewald's formula, even when TG is above 800 mg/dL ( 45 , 46 ). Given the above reasons, it is reasonable to estimate RC using the Sampson formula.…”
Section: Discussionmentioning
confidence: 99%
“…The new Sampson formula reported by Sampson et al is a better alternative for estimating LDL-C than conventional methods ( 18 ). Quite a few studies proved that Sampson's formula is more accurate than Friedewald's formula, even when TG is above 800 mg/dL ( 45 , 46 ). Given the above reasons, it is reasonable to estimate RC using the Sampson formula.…”
Section: Discussionmentioning
confidence: 99%
“…Sajja et al [28] concluded that the Martin/Hopkins equation offers higher LDL-C accuracy than the Sampson equation in patients with high TG levels within the range of 4.5−9 mmol/l. In a study carried out in a group of 6701 healthy patients, Cao et al [29] support the replacement of the Friedewald equation with either the Martin-Hopkins or Sampson formula in the general population as the Martin-Hopkins and Sampson formulae did not over or underestimate ASCVD (atherosclerotic cardiovascular disease) Srisk.…”
Section: Methodsmentioning
confidence: 99%
“…Sajja et al [28] concluded that the Martin/ Hopkins equation offers higher LDL-C accuracy than the Sampson equation in patients with high TG levels within the range of 4.5À9 mmol/l. In a study carried out in a group of 6701 healthy patients, Cao et al [29] support the replacement of the Friedewald equation with either the Martin-Hopkins or Sampson formula in the general population as the Martin-Hopkins and The difference between the correlation coefficients was statistically significant Good correlation was also seen with LDL-C levels <1mmol/l as seen in patients on PCSK9 inhibitors When TG levels are >1.7 mmol/l which occurs in the top 25--30% of the population, the NIH Eq.…”
Section: Comparison Of Martin/hopkins and Sampson/national Institutes...mentioning
confidence: 99%
“…Importantly, a nonfasting state did not change the performance of the Martin/Hopkins method but reduced the accuracy of the Sampson/NIH formula. 14 In another work, the authors demonstrated clinically meaningful differences in LDL-c calculated by different formulas in patients with ASCVD. LDL-c was usually higher with the Martin/Hopkins equation, suggesting a higher rate of LDL-c underestimation with the Friedewald and Sampson/NIH methods.…”
mentioning
confidence: 92%
“…In this sense, evidence from two large databases using directly measured LDL-c as the comparator favored the Martin/Hopkins approach, 11,12 whereas a smaller study found that the Sampson/NIH formula had higher concordance with LDL-c estimated using VLDL-c measured by ultracentrifugation in individuals with familial combined hyperlipidemia. 13 Two recent studies published by Sajja et al 14,15 from Johns Hopkins University have raised concerns about the Sampson/NIH method. In one of them, the authors showed that an extended version of the Martin/Hopkins equation had better accuracy than the Friedewald and Sampson/ NIH formulas in individuals with TG levels of 400 to 799 mg/dL.…”
mentioning
confidence: 99%